Analysis of Judge's Decision in Corruption Crimes (Study of Decision Number 2205 K/Pid.Sus/2022) - Zufriansyah, Mohammad; Hafidz, Jawade (UNISSULA Semarang, 2025)
The eradication of corruption has not been carried out optimally, where the prosecutor's office often fails to win corruption cases, until the defendant is acquitted. One example of an acquittal for corruption in Decision Number 2205 K / Pid.Sus / 2022. This study aims to determine and analyze the judge's decision in corruption in Decision Number 2205 K / Pid.Sus / 2022 and the basis for the judge's considerations in making a decision on corruption in Decision Number 2205 K / Pid.Sus / 2022. This study uses a normative legal approach method, the research specification is descriptive analytical. The data used are primary data and secondary data while the data collection method is carried out through field studies and literature studies. The data analysis method is qualitative. TThe theories used are the theory of punishment, the theory of justice and the theory of legal certainty. Based on the research results it can be concluded that iImplementation of restorative justice in resolving traffic accidents The judge's decision in the corruption case in Decision Number 2205 K/Pid.Sus/2022 reflects a bad precedent in enforcing corruption law in Indonesia, where the cassation level decision upheld the first level judge's decision, namely that the defendant Samin Tan was declared not legally and convincingly proven to have committed a crime in the first or second indictment and was declared free from all legal charges. The judge in his consideration was not quite right, where the perpetrator should have been punished under Article 5 paragraph (1) of the Corruption Law or Article 13 of the Corruption Law, but the judge stated that the defendant's actions were those of a gratification giver so that he could not be subject to criminal penalties. The breakdown of the elements in the Samin Tan decision did not look at the legal facts directly, because the focus was only on the absence of regulations for the gratification giver, so the judge stated that the defendant was not proven to have committed the crime charged and was declared free.